Enzymatic degradation of uracil-containing DNA. II. Evidence for N-glycosidase and nuclease activities in unfractionated extracts of Bacillus subtilis. - Duncan, J (1976)
Further studies have confirmed our earlier observations that in the presence of EDTA, degradation of phage PBS2 [3H]uracil-labeled DNA is effected by an N-glycosidase activity in extracts of Bacillus subtilis that removes free uracil from DNA. In addition, such extracts contain a nuclease activity that attacks PBS2 DNA in the presence of CaCl2. The nuclease activity is not observed under conditions that inactivate N-glycosidase activity but does attack DNA that has been preincubated to remove uracil by N-glycosidase action. We therefore postulate that the nuclease requires N-glycosidase action to generate substrate for its activity, i.e., the nuclease appears to attack depyrimidinated sites rather than uracil sites in phage PBS2 DNA.